Enhancing the Quality of Physical Culture Education: Exploring the Role of Communicative Competence in Physical Culture Teachers - Yurij Vaskov (Physical Culture, Recreation and Rehabilitation)
Background and study aim. Effective communication is crucial for teachers in ensuring a high-quality educational process. This study aims to analyze the communicative competence of physical culture teachers and its contribution to the quality of the educational process in their lessons.